Hermetic Seal of Organic Light Emitting Diode with Glass Frit - Chien-Liang Chiu; Meng-Syun Lin; Yi-Chen Wu (Molecules, 2021)
The components of OLED encapsulation with hermetic sealing and a 1026-day lifetime were measured by PXI-1033. The optimal characteristics were obtained when the thickness of the TPBi layer was 20 nm. This OLED obtained a maximum luminance (Lmax) of 25,849 cd/m2 at a current density of 1242 mA/cm2, an external quantum efficiency (EQE) of 2.28%, a current efficiency (CE) of 7.20 cd/A, and a power efficiency (PE) of 5.28 lm/W. The efficiency was enhanced by Lmax 17.2%/EQE 0.89%/CE 42.1%/PE 41.9%. The CIE coordinates of 0.32, 0.54 were all green OLED elements with wavelengths of 532 nm. The shear strain and leakage test gave results of 16 kgf and 8.92 × 10−9 mbar/s, respectively. The reliability test showed that the standard of MIL-STD-883 was obtained.